Globalisasi, Pasca-Sekularisme, dan Pergeseran Batas-Batas Sakral - Arnel, Iskandar; Haq, Mochamad Ziaul; Haqq, Muhammad Valiyyul (Faculty of Ushuluddin UIN Sunan Gunung Djati Bandung, 2024)
The aim of this paper is not to close the dots through the imposition of a single understanding. The author simply wants to highlight significant points of ‘contestation’ in the way we understand or even blur the boundaries between the religious and the political. This research uses a qualitative method that is based on a literature study. We conclude that there are multiple and sometimes competing understandings of terms such as religion, secularism, secularisation and post-secular that shape and are shaped by discussions about the relationship between religion, politics and public life. For future researchers, we suggest exploring the correlation between religion, politics and the public sphere more specifically in order to create a paradigm that does not corner one another so that there is no overlap in understanding these three elements.